Category Shift in English-Indonesian “The Lion King” Movie Subtitle - Gaudensius Jordan De Martin; Ni Luh Ketut Mas Indrawati; Galuh Febri Putra (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study investigates category shifts in the Indonesian subtitle translation of The Lion King (2019) using a combination of qualitative and quantitative methods. Drawing on Catford’s Category Shift Theory (1965), the research identifies four types of shifts—structure, class, unit, and intra-system—within the film’s subtitles. The data, collected through documentation and note-taking techniques, were analyzed to determine the nature and frequency of each shift type. The findings show that structure shifts are the most dominant (54%), followed by unit shifts (21%), class shifts (18%), and intra-system shifts (7%). These shifts demonstrate the translator’s strategy in adapting the source language to suit the target language's syntactic and semantic norms. By focusing on the linguistic and functional aspects of subtitle translation, this research highlights the importance of translation shifts in maintaining clarity, naturalness, and audience engagement in cross-linguistic audiovisual media.